ANALISIS KUALITAS PELAYANAN PUBLIK TERHADAP MASYARAKAT DI DESA KLAPANUNGGAL KECAMATAN KLAPANUNGGAL KABUPATEN BOGOR - M. Zairin; Surya Purnama Adi; Zeze Zakaria Hamzah; Muhlis (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2024)
This study aims to determine the quality of public services on community satisfaction in Klapanunggal Village, Klapanunggal District, Bogor Regency. This research uses quantitative methods with a descriptive approach, and by providing a systematic and accurate description of the perceptions, the community about the quality of public services provided by Klapanunggal Village, Klapanunggal District, Bogor Regency. The results of the analysis with the Service Quality (SQ) method show that there is a gap in all elements of public services, which means that the community is not satisfied with the quality of public services provided by Klapanunggal Village. While the level of community satisfaction calculated using the Customer Satisfaction Index (CSI) method shows a result of 76.2%, meaning that it is included in the category of people feeling quite satisfied with the quality of public services in Klapanunggal Village, but not yet very satisfied. Furthermore, based on the results of the analysis with the Cartesian diagram of the Importance Performance Analysis (IPA) method, it is known that the service indicators included in the top priority (Quadrant A) to be improved in order to increase community satisfaction in the future are indicators P6 (competence / ability of officers), P8 (handling complaints) and P9 (quality of facilities and infrastructure).